In vitro cytotoxicity, cellular uptake, reactive oxygen species and cell cycle arrest studies of novel ruthenium(II) polypyridyl complexes towards A549 lung cancer cell line. (4th May 2021) - Qasim Warraich, Muhammad; Ghion, Alessandra; Perdisatt, Laura; O'Neill, Luke; Casey, Alan; O'Connor, Christine
Abstract: Ruthenium(II) polypyridyl complexes have displayed some promising biological responses against a variety of cancers and have emerged as a potential candidate that can show significant antitumor activity. Three ruthenium(II) polypyridyl complexes were biologically evaluated in vitro against the A549 cancer cell line. The complexes were selected based on initial DNA intercalation studies and MTT viability screening and were selected based on the most promising candidates, the [Ru(bpy)2 o -CPIP].2PF6 (complex 1), [Ru(phen)2 o -CPIP].2PF6 (complex 2) and [Ru(biq)2 o -CPIP].2PF6 (complex 3). Confocal cellular uptake studies confirmed the intracellular transport of complexes into A549. Cytoplasmic and the nucleic accumulation of the complex 1 and 2 was seen while no fluorescent microscopy was performed for complex 3 due to instrumental limitations. Cellular cytotoxicity was investigated with the aid of the Alamar blue assay. The complexes displayed concentration and time dependent inhibitory effects yielding IC50 values from 5.00 to 32.75 µM. Complex 1 exhibit highest cytotoxicity with IC50 value of 5.00 ± 1.24 µM. All of the complexes have shown a significant effect in the reduction of intracellular reactive oxygen species (ROS) levels. Finally, the complexes have shown a transient effect on the cell cycle by arresting it at G0/G1 phase except for complex 2 [Ru(phen)2 o -CPIP].2PF6 which has shown the significant G0/G1 arrest.